TELAAH POLIGINI: PERSPEKTIF ULAMA POPULER DUNIA (Dari Ulama Klasik Hingga Ulama Kontemporer) - Fathonah Fathonah (Al Hikmah: Jurnal Studi Keislaman, 2015)
Polygyny has been a debate among Islamic jurists (fuqaha') from the classic to the modern era. Even West also criticized polygyny and denounced Islam as a religion of gender bias. This paper is to analyze the long debate on this issue by some scholars the world, and emphasize what form of marriage that is actually commanded by the Quran and al-Hadith? Popular scholar opinion in the world about polygyny that have been initiated since the classical era to the contemporary era is an important scientific treasures that should be known to the public, so that the message of the polygamy verse (al-Nisa [4]: 3) can be understood with a wise and there is no prejudice against Islam. Similarly, the implementation of polygyny can be tightened, so it is not easily diverted and no impression act of despotic against women. Opinions of scholars the world here from various disciplines, from islamic jurists, exegetes (mufassirun) and linguists. From the classic to the contemporary era.